Approach to the canine coxofemoral joint using an osteotomy of the deep gluteal muscle insertion for total hip replacements - Tardiani, Lauren; Goldsmid, Sarah; Lanz, Otto (Frontiers in Veterinary Science, 2023)
Canine total hip replacements (THR) are commonly performed using a craniolateral approach to the craniodorsal aspect of the hip which traditionally involves a partial deep gluteal tendon tenotomy (DGT). Performing an osteotomy of the insertion of the deep gluteal tendon has been utilized by some surgeons. Utilizing bone healing over tendon healing aims to improve post operative hip stability. To the authors' knowledge, this is the first published description of the novel deep gluteal osteotomy (DGO) approach. It differs from a greater trochanteric osteotomy as the latter involves an osteotomy of both the deep and middle gluteal insertions. DGT and the novel DGO approach were performed in ten medium to large breed cadavers on contralateral limbs. The surface area of acetabular exposure was measured in contralateral limbs following the approaches and the iatrogenic damage to the deep gluteal, middle gluteal and vastus lateralis muscles following femoral reaming was visually graded (none, mild, moderate or severe) based on muscle proportion damaged. There was no statistically significant difference (p = 0.8223) between the surface area of acetabular cartilage exposed by each approach with the mean surface area for the DGO approach being 2.99 cm 2 , whilst the mean surface area for the DGT was 2.97 cm 2 . In 80% of cadavers, the DGO approach achieved lower muscle damage following retraction and femoral reaming compared to the DGT approach for the middle gluteal and deep gluteal muscles (p = 0.0073). In all cadavers, overall muscle damage was lower for the DGO approach compared to the DGT approach (p = <0.001). There was no difference in vastus lateralis damage between procedures. The DGO approach may be a reasonable alternative to the DGT for approaching the hip joint and femur for Zurich THR as it provides similar exposure to the acetabulum with less muscle damage. It relies on more reliable osseous healing compared to tendon healing. Reduced muscle damage may be important for postoperative hip stability following THR.Further studies are required to biomechanically assess the strength of DGO repair compared to DGT repair as well as a case series documenting clinical outcomes.